Topography of lacUV5 initiation complexes - Studitsky, Vasily M. (Oxford University Press, 2001)
Formation of a transcriptionally competent open complex is a highly regulated multistep process involving at least two intermediates. The rate of formation and stability of the intermediate complexes often determine promoter strength. However, the detailed mechanism of formation of the open complex and the high resolution structures of these intermediates are not known. In this study the structures of the open and intermediate complexes formed on the lacUV5 promoter by Escherichia coli RNA polymerase were analyzed using ‘zero length’ DNA–protein cross-linking. In both the open and the intermediate complexes the core subunits (β′ and β) interact with lacUV5 DNA in a similar way, forming DNA–protein contacts flanking the initiation site. At the same time, the recognition (σ(70)) subunit closely interacts with the promoter only in the open complex. In combination with our previous results, the data suggest that during promoter recognition contacts of the σ subunit with core RNA polymerase and promoter DNA are rearranged in concert. These rearrangements constitute a landmark of transition from the intermediate to the open complex, identifying the σ subunit as a key player directing formation of the open complex.